Brazilian consensus recommendations for the diagnosis, screening, and treatment of individuals with fabry disease: Committee for Rare Diseases - Brazilian Society of Nephrology/2021 - Silva, Cassiano Augusto Braga; Andrade, Luis Gustavo Modelli De [UNESP]; Vaisbich, Maria Helena; Barreto, Fellype De Carvalho (Sociedade Brasileira de Nefrologia, 2022)
Fabry disease (FD) is an X-linked inherited disorder caused by mutations in the GLA gene encoding enzyme alpha-galactosidase A (α-Gal A). The purpose of this study was to produce a consensus statement to standardize the recommendations concerning kidney involvement in FD and provide advice on the diagnosis, screening, and treatment of adult and pediatric patients. This consensus document was organized from an initiative led by the Committee for Rare Diseases (Comdora) of the Brazilian Society of Nephrology (SBN). The review considered randomized clinical trials, real-world data studies, and the expertise of its authors. The purpose of this consensus statement is to help manage patient and physician expectations concerning the outcomes of treatment. Our recommendations must be interpreted within the context of available evidence. The decisions pertaining to each individual case must be made with the involvement of patients and their families and take into account not only the potential cost of treatment, but also concurrent conditions and personal preferences. The Comdora intends to update these recommendations regularly so as to reflect recent literature evidence, real-world data, and appreciate the professional experience of those involved. This consensus document establishes clear criteria for the diagnosis of FD and for when to start or stop specific therapies or adjuvant measures, to thus advise the medical community and standardize clinical practice.
Keywords: Fabry Disease; Consensus; Rare Diseases